X-ray spectroscopic studies of the electronic structure of chromium-based p-type transparent conducting oxides - FLEISCHER, KARSTEN; NORTON, EMMA; CALLAGHAN, STEPHEN; MCGUINNESS, CORMAC; FARRELL, LEO; SHVETS, IGOR (My University, 2016)
The valence band structure of p-type transparent oxides—crystalline MgxCr2−xO3 and nanocrystalline CuxCrOy—is analyzed as a function of incoming photon energy. The valence band of both p-type transparent conducting oxides shows striking similarities to measurements on crystalline CuCrO2:Mg with all films showing that chromium states compose the top of the valence band, suggesting that the valence-band structure is dominated by the presence of the Cr-O6 octahedra. A comparison of the valence band between the best performing p-type, crystalline CuCrO2:Mg, with crystalline MgxCr2−xO3 and nanocrystalline CuxCrOy shows that the chromium 3d states are fixed irrespective of changes in long-range crystallographic order. This indicates little spatial overlap between adjacent Cr 3d states. This further confirms the conduction mechanism via hopping for chromium based p-type TCOs as the Cr 3d states are localized within the Cr-O6 octahedra.
PUBLISHED
Keywords: Nanoscience & Materials; Smart & Sustainable Planet; TRANSPORT MEASUREMENTS; TRANSPORT PROPERTIES; Transparent Conducting Oxide; XPS